The Law of Full Control of Debt Security Objects by Murtahin Perspective Wahbah az-Zuhaili (Study in Riau, Indonesia) - Nabila, Tiara; Khamal Rokan, Mustafa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to find out the law related to the occurrence of full control of the debt collateral object by the murtahin (debt giver). The method used in this research is an empirical juridical research method obtained through interviews. As for the research location in Bathin Betuah Village, Mandau District, Bengkalis Regency, Riau, the perspective used is the opinion of Wahbah az-Zuhaili. The approach used is a conceptual approach . The research results show that control of the debt collateral object may not be fully controlled by the murtahin. This is because Rahin is unable to pay his debt installments, always asks for time to pay his debts, and does not keep his promise to pay at the specified time. Murtahin's full control of the debt collateral object must not be separated from its original owner (Ar-Raahin) and Al-Murtahin may not own it, when Ar-Raahin is unable to redeem it at the specified time. The solution offered when Rahin is no longer able to pay the debt is that the proceeds from the sale of the collateral object are to pay the debt. If the debt has been paid off and there is an excess (remaining) then it becomes the property of Rahin (the borrower). According to Wahbah az-Zuhaili, the practice of controlling debt collateral completely by murtahin is not permitted or is haram.